Nanotheranostics: Emerging strategies for early diagnosis and therapy of brain cancer - Sonali; Viswanadh, M.K.; Singh, R.P.; Agrawal, P.; Mehata, A.K.; Pawde, D.M.; Narendra; Sonkar, R.; Muthu, M.S. (Ivyspring International Publisher, 2018)
Nanotheranostics have demonstrated the development of advanced platforms that can diagnose brain cancer at early stages, initiate first-line therapy, monitor it, and if needed, rapidly start subsequent treatments. In brain nanotheranostics, therapeutic as well as diagnostic entities are loaded in a single nanoplatform, which can be further developed as a clinical formulation for targeting various modes of brain cancer. In the present review, we concerned about theranostic nanosystems established till now in the research field. These include gold nanoparticles, carbon nanotubes, magnetic nanoparticles, mesoporous silica nanoparticles, quantum dots, polymeric nanoparticles, upconversion nanoparticles, polymeric micelles, solid lipid nanoparticles and dendrimers for the advanced detection and treatment of brain cancer with advanced features. Also, we included the role of three-dimensional models of the BBB and cancer stem cell concept for the advanced characterization of nanotheranostic systems for the unification of diagnosis and treatment of brain cancer. In future, brain nanotheranostics will be able to provide personalized treatment which can make brain cancer even remediable or at least treatable at the primary stages. © Ivyspring International Publisher.
Keywords: brain cancer; cancer nanotechnology; drug delivery; molecular biomaterial; molecular imaging; targeting